Fuentes fenomenológicas de la noción de persona: su discusión en Husserl, Scheler y Heidegger - Muñoz, Enrique (2012)
“Phenomenological Sources for the Concept of Person: their Discussion in the Works of Husserl, Scheler and Heidegger”. The article sets out to reconstruct the arguments that are developed by Heidegger on the concept of the person in some passages of § 10 of Being and Time. In those brief passages, Heidegger comments positively on the concept of the person as elucidated by Husserl and Scheler in the framework of the phenomenological movement. Consequently, in the article, I focus on identifying and commenting on the principal arguments of Husserl’s Ideas II and Scheler’s Ethics and Book of Sympathy, from which it is possible to hold the known thesis that the person is neither object, nor substance. Finally, I explore some of the different shades presented by the authors regarding the concept of the person.